A systematic review and meta‐analysis of robotic resections for diverticular disease. (9th August 2022) - Larkins, Kirsten; Mohan, Helen; Apte, Sameer S.; Chen, Vicky; Rajkomar, Amrish; Larach, José Tomás; Smart, Philip; Heriot, Alexander; Warrier, Satish
Abstract: Aim: Resection of diverticular disease can be technically challenging. Tissue planes can be difficult to identify intraoperatively due to inflammation or fibrosis. Robotic surgery may improve identification of tissue planes and dissection which can facilitate difficult minimally invasive resections. This systematic review and meta‐analysis evaluates the role of robotic surgery compared to laparoscopic surgery in diverticular resection. Methods: A systematic review and meta‐analysis was performed in accordance with the PRISMA statement. The search was completed using PubMed, OVID MEDLINE and EMBASE. A total of 490 articles were retrieved, and studies reporting primary outcomes for robotic diverticular resection were included in the final analysis. A meta‐analysis of studies comparing robotic and laparoscopic surgery was performed on rate of conversion to open surgery and complications. Results: Fifteen articles (8 cohort studies and 7 case series) reporting 3711 robotic diverticular resections were analysed. In comparison to laparoscopic, robotic surgery for diverticular disease was associated with a reduced conversion to open and a longer operating time. Meta‐analysis showed robotic resection was associated with a lower conversion rate compared to laparoscopic surgery (OR: 0.57; 95% CI: 0.49–0.66, p  < 0.001). There was no significant difference in grade III and above complications (OR: 0.74; 95% CI: 0.49–1.13, p  = 0.17). Operating time was longer with a robotic approach (Hedge's G: 0.43; 95% CI: 0.04–0.81, p  = 0.03). Conclusion: Robotic resection is a feasible and safe option in diverticular disease. Although associated with a longer operating time, robotic surgery may render diverticular disease resectable with a minimally invasive approach that would have otherwise necessitated a laparotomy. Randomised controlled data is required to better define the role of robotic surgery for diverticular disease resections.